Modeling Inflation in Chad - Kinda, Tidiane (IMF Working Papers; Working Paper ;, 2011)
This paper examines the determinants of inflation in Chad using quarterly data from 1983:Q1 to 2009:Q3. The analysis is based on a single-equation model, completed by a structural vector auto regression model to capture inflation persistence. The results show that the main determinants of inflation in Chad are rainfall, foreign prices, exchange rate movements, and public spending. The effects of rainfall shocks and changes in foreign prices on inflation persist during six quarters. Changes in public spending and the nominal exchange rate affect inflation during three and four quarters, respectively.